Role of family, school, peers and community in the adaptation process of young immigrants - Deslandes, Rollande (International Journal about Parents in Education, 2023)
Using a qualitative methodology, this study investigated the extent to which immigrant school-age children have adapted to their new “home” in Quebec, particularly in terms of development of healthy lifestyles and life skills and how their families, schools and other environmental environment shave contributed to their adaptation process. Semi-structured interviews groups were conducted with young children aged 8-13 years and their parents who have immigrated in the Mauricie region 2 to 5 years ago. Findings highlight the complementary roles of the various environmental milieus of the immigrant child. Parents, mainly mothers, have a major influence on eating habits while the school and teachers are uniquely positioned to promote physical activity, French language learning and friendship development. Children agree that the teachers encourage and help them to develop their life skills, but nevertheless credit their parents with being the primary influence. Avenues for interventions and future studies are being discussed.